The impact of expressing mixed valence emotions in organizational crisis communication on consumer’s negative word-of-mouth intention - Xiao, Yi; Hudders, Liselot; Claeys, An-Sofie; Cauberghe, Verolien (Public relations review, 2018)
•Expressing each discrete emotion or emotion with mixed valence in crises can play a different role in affecting stakeholders’ reactions.•The effects of expressing emotions with mixed valence versus single valence are moderated by crisis type.•The effects of expressing emotions with mixed valence in crisis can be mediated by perceived sincerity and perceived empathy towards the spokesperson.•Expressing emotions with mixed valence elicits higher perceived sincerity and more empathy towards the spokesperson in preventable crisis.•Expressing anger results in less negative word of mouth through an increase in perceived sincerity and empathy towards the spokesperson in victim crisis. This paper examines the impact of expressing different discrete emotions with a mixed valence (anger and hope) in organizational crisis communication on negative word-of-mouth on social media. In particular, the effects of expressing discrete emotions with a single valence (either positive or negative) versus mixed valence (expressing both positive and negative emotions) emotions are studied by means of a 4 (emotional message framing: control vs. positive emotion vs. negative emotion vs. mixed valence emotions) by 2 (crisis type: victim vs. preventable crisis) between-subjects experimental design (N = 295). Results show that in a preventable crisis, expressing mixed valence emotions elicits higher perceived sincerity and more empathy towards the spokesperson, and subsequently less negative word-of-mouth compared to expressing either single emotions or the control condition. However, in the case of a victim crisis, expressing single emotions, and especially a negative emotion like anger, results in less negative word-of-mouth through an increase in perceived sincerity and empathy towards the spokesperson.